In Silico Molecular Docking Studies of Cell-Penetrating Peptide and Doxorubicin toward Multiple Tumor Receptors - Soni, Vandana (Asian Journal of Pharmaceutics (AJP), 2024)
Molecular docking, a powerful computational tool, is revolutionizing drug discovery by illuminating the intricate dance between ligands and proteins. This research delves deep into this molecular tango, analyzing how various ligands interact with key disease-linked proteins. The study employed molecular docking to assess the binding affinity and interaction modes of a novel peptide and doxorubicin across diverse target proteins. The peptide emerged as a star performer, exhibiting remarkably strong binding to crucial proteins such as HER3 kinase (−11.906 docking score) and VEGFR (−7.609 docking score). These impressive scores suggest the peptide’s potential as a potent inhibitor for these proteins, potentially disrupting critical cancer pathways. In contrast, doxorubicin displayed significantly weaker binding across all targets, highlighting its potential limitations as an inhibitor. The study further explored the influence of ligand structure and chemical properties on their binding specificity, shedding light on the molecular determinants governing these interactions. By harnessing the power of molecular docking, the research ventured into the exciting realm of rational drug design and virtual screening. Identifying key amino acid residues involved in ligand binding paved the way for designing novel ligands with enhanced binding affinities and improved selectivity profiles. This research paves the way for a deeper understanding of drug-protein interactions at the molecular level, ultimately fostering the development of more effective and targeted therapeutic agents for various diseases.